AKULTURASI BUDAYA KEAGAMAAN DI CINA BENTENG KOTA TANGERANG - Haryani, Elma (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2020)
The existence of Chinese ethnic in Indonesia has been going on for centuries. Pro and contra attitudes emerge from other Indonesian societies because of the seriousness of the Chinese ethnic group to integrate with other communities is often doubted. This study tries to discuss the religious culture of the Chinese people in the Indonesian context. Research question is formulated to answer how the Benteng Chinese community built a religious culture to remain united with other ethnic groups in Indonesia. This study is a qualitative research with a case study approach. The case chosen was the Chinese ethnic group in Benteng Chinese Tangerang. The results of the study show that the Benteng Chinese community has succeeded in building religious cultural resilience in such a way that the Benteng Chinese community continues to exist today. The model of religious culture resilience that is built is to build religious and cultural accuracy in a dialogical way. This dialogical model in acculturation of culture and religion is a more peaceful solution compared to the social history of the Chinese ethnic groups in Indonesia which is indicated by conflict and violence. Keywords: acculturation, Cina Benteng, religious culture, Tangerang Â Keberadaan suku Tionghoa di Indonesia telah eksis selama berabad-abad. Sikap pro dan kontra muncul dari masyarakat indonesia lainnya, demikian juga kesungguhan suku Tionghoa menyatu dengan masyarakat lainnya juga sering diragukan. Tulisan ini mencoba membahas budaya keagamaan suku Tionghoa dalam konteks keindonesiaan. Permasalahan penelitian dirumuskan untuk menjawab bagaimana masyarakat Cina benteng membangun budaya keagamaan untuk tetap bisa menyatu dengan suku bangsa yang lain di Indonesia. Kajian ini merupakan jenis penelitian kualitatif dengan pendekatan studi kasus. Kasus yang dipilih adalah suku Tionghoa di Cina Benteng Tangerang. Hasil kajian menunjukkan bahwa masyarakat Cina Benteng berhasil membangun ketahanan budaya keagamaan sedemikian rupa sehingga komunitas Cina Benteng ini tetap eksis hingga sekarang. Model ketahanan budaya keagamaan yang dibangun adalah membangun alkuturasi agama dan budaya secara dialogis. Model dialogis dalam akulturasi budaya dan agama ini menjadi jalan keluar yang lebih damai dibandingkan dengan sejarah sosial suku Tionghoa di Indonesia yang diwarnai gambaran konflik dan kekerasan. Kata Kunci: akulturasi, budaya keagamaan, Cina Benteng, Tangerang